2021
DOI: 10.3324/haematol.2020.248542
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, molecular and clinical aspects of coagulation factor VII and its role in hemostasis and thrombosis

Abstract: Activated factor VII (FVIIa), the first protease of clotting, expresses its physiological procoagulant potential only after complexing with tissue factor (TF) exposed to blood. Deep knowledge of the FVIIa-TF complex and F7 gene helps to understand the Janus-faced clinical findings associated to low or elevated FVII activity (FVIIc). Congenital FVII deficiency, the most frequent among the recessively inherited bleeding disorders, is caused by heterogeneous mutations in the F7 gene. Complete FVII deficiency caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 106 publications
(163 reference statements)
7
70
0
Order By: Relevance
“…The analysis of clinical phenotypes in 37 homozygotes for the p.A354V-p.P464Hfs variant significantly extends previous information about variability in bleeding severity in FVII-deficient patients. The small range of FVII:C in a group of patients with the same F7 genotype supports the notion that a large variation in clinical phenotypes is detectable with relatively small variations in FVII activity, a major open question in FVII deficiency [3]. The investigation of FVII:Ag in plasma revealed that the antigen levels were clearly higher than the activity levels, suggesting a Type-II defect.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The analysis of clinical phenotypes in 37 homozygotes for the p.A354V-p.P464Hfs variant significantly extends previous information about variability in bleeding severity in FVII-deficient patients. The small range of FVII:C in a group of patients with the same F7 genotype supports the notion that a large variation in clinical phenotypes is detectable with relatively small variations in FVII activity, a major open question in FVII deficiency [3]. The investigation of FVII:Ag in plasma revealed that the antigen levels were clearly higher than the activity levels, suggesting a Type-II defect.…”
Section: Discussionsupporting
confidence: 61%
“…Factor (F) VII is a vitamin K-dependent glycoprotein synthesized in the liver that undergoes extensive post-translational modifications prior to secretion [1][2][3]. It is secreted into the blood where it circulates at a concentration of roughly 0.5 µg/mL (10 nM) [4].…”
Section: Introductionmentioning
confidence: 99%
“…It can present as type I which is a quantitative defect or type II being the qualitative defect with the latter having normal factor VII antigen while the former presenting with both low FVII:C and FVII:Ag [4]. The factor VII gene is located at chromosome 13q34 and several mutations within this gene lead to low levels of FVII [2,6]. Clinically the symptoms do not tally with the levels of FVII with some patients having mild to moderate deficiency but presenting with severe bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Proteases are central to numerous biological pathways and play a vital role in regulating many signaling processes, such as cell-cycle progression [ 5 ], cell proliferation [ 6 ], cell death [ 7 ], DNA replication [ 8 ], tissue remodeling [ 9 ], hemostasis [ 10 ], wound healing [ 11 ], and immune responses [ 11 ]. Consistent with their essential roles, alterations in proteolytic systems result in multiple pathological conditions, including cancer [ 12 ], neurodegenerative disorders [ 13 ], infections [ 13 ], allergies [ 14 ], blood clotting disorders [ 15 ], and cardiovascular diseases [ 16 ]. Given the enormity of proteolytic potential, protease activity must be tightly regulated to prevent inappropriate and frequently destructive proteolysis.…”
Section: Introductionmentioning
confidence: 99%